The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1073/pnas.94.15.8156
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest of Epstein–Barr virus immortalized B lymphocytes by adenovirus-delivered ribozymes

Abstract: Epstein-Barr virus (EBV) infection is associated with several human diseases that involve unrestricted proliferation of B lymphocytes. EBV nuclear antigen 1 (EBNA-1) is expressed in all EBV-infected cells and plays an essential role in persistence of the EBV genome. EBNA-1 has also been reported to have oncogenic potential. As an approach for treating EBV infections, we examined the capacity of EBNA-1 ribozymes delivered by recombinant adenoviruses to suppress EBNA-1 expression and to block virus-induced B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 33 publications
4
34
1
Order By: Relevance
“…Then, replication-deficient adenovirus type 5 encoding green fluorescent protein (GFP) was added to the cell suspension at a multiplicity of infection (m.o.i.) of 50 or 500 (45). After 1 h at 37°C, virus not internalized was digested by incubation of the cells with 0.03% trypsin and 0.35 mM EDTA for 5 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Then, replication-deficient adenovirus type 5 encoding green fluorescent protein (GFP) was added to the cell suspension at a multiplicity of infection (m.o.i.) of 50 or 500 (45). After 1 h at 37°C, virus not internalized was digested by incubation of the cells with 0.03% trypsin and 0.35 mM EDTA for 5 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, EBNA1 has little effect on transcription of an EBNA1-dependent reporter integrated at most sites in cell DNA (20,29). Alternatively, EBNA1 might alter cell growth or survival through an interaction with a cell protein (30)(31)(32)(33)(34)(35)(36)(37)(38)(39). However, once EBV DNA has integrated into cell DNA, EBNA1 is not required for LCL growth, and LCLs with EBNA1-null mutant EBV genomes are indistinguishable from wild-type EBV-transformed B lymphocytes in their growth (12).…”
mentioning
confidence: 99%
“…This initially suggested to us that the RGD sequence was important for mediating viral transduction of murine B cells as has been shown for human B cells. 3,7,14 However, inhibition studies (shown in Figure 9) did not reveal a major role for RGD-integrin interactions in the transduction of LPS-activated B cells. Other possibilities include (1) the fiber knob of the Adz.PB(FLAG) may cause steric hindrance of the anti-FLAG antibody from interacting effectively with both the FLAG epitope and the Fc receptor 17 or (2) the sequence of the penton base near the RGD motifs is important for interactions with unknown cell surface proteins.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Adenovirus infects a host cell by interaction of at least two coat proteins with two cell surface receptors. The fiber protein interacts with the coxsackievirus-adenovirus receptor 3 (CAR).…”
Section: Introductionmentioning
confidence: 99%